Alleles Causing Resistance to Isoxaben and Flupoxam Highlight the Significance of Transmembrane Domains for CESA Protein Function - Shim, Isaac; Law, Robert; Kileeg, Zachary; Stronghill, Patricia; Northey, Julian G. B.; Strap, Janice L.; Bonetta, Dario T. (Frontiers in Plant Science, 2018)
The cellulose synthase (CESA) proteins in Arabidopsis play an essential role in the production of cellulose in the cell walls. Herbicides like isoxaben and flupoxam specifically target this process and are potent cellulose biosynthesis inhibitors (CBIs). Forward genetic screens in Arabidopsis revealed that novel mutations resulting in varying degrees of resistance to either CBI can be attributed to single amino acid substitutions in primary wall CESAs. Missense mutations are almost exclusively in the predicted transmembrane regions of CESA1 and CESA3, and CESA6. Resistance to isoxaben was also conferred by modification to the catalytic residues of CESA3. This resulted in cellulose deficient phenotypes characterized by reduced crystallinity and dwarfism. However, mutations mapping to the transmembrane regions also lead to growth phenotypes and altered cellulose crystallinity phenotypes. These results provide further genetic evidence supporting the involvement of CESA transmembrane regions in cellulose biosynthesis.